METHODOLOGY OF TEACHING PROFESSIONAL COMMUNICATION IN A FOREIGN LANGUAGE FOR STUDENTS OF AGRICULTURAL EDUCATION FIELDS - Nuratdinova Jupargul Satbaevna (Galaxy International Interdisciplinary Research Journal, 2023)
Еven for all students, in particular students of the agricultural direction, excellent knowledge of a foreign language, the development of their professional skills, comprehensive study and research of innovations in the field are one of the priority tasks. Nowadays, the demand for the agricultural sector in particular has increased more than ever. Raising the level of knowledge of students to a higher level, raising them in every possible way, ensuring their further growth mentally in a positive sense is the first task pursued in the realization of the goal set for teaching a foreign language. The article presents ideas about the methodology for teaching professional communication in a foreign language, the development of professional skills and abilities for students of the field of agricultural education.